Outcome of Type 1 Tympanoplasty with and without the use of Topical Nasal Steroid: A Comparative Study from Eastern Nepal - Shah, Rajeev Kumar; Shrestha, Karuna; Sapkota, Shrijana; Giri, Sandarva (Birat Journal of Health Sciences, 2018)
Introduction: Chronic suppurative otitis media (CSOM) is the infection of the middle ear cleft. It is an important cause of preventable hearing loss. Objectives: The primary objective of this study is to compare the surgery outcome in terms of graft uptake described as intact tympanic membrane or residual perforation of tympanic membrane in patients with use of levocetirizine tablet 5 milligram only and levocetirizine tablet 5 milligram with topical fluticasone 100 microgram nasal steroid spray. This study is also aimed to determine the hearing status before and after the surgery and to find out its association with graft intake. Methodology: This prospective cross sectional study was conducted on patients diagnosed with chronic suppurative otitis media with medium to large central perforation of tympanic membrane in Birat Medical College Teaching Hospital during the period from 14 April 2015 to 13 April 2017. All the patients underwent type 1 tympanoplasty with placement of temporalis fascia under general anesthesia. After surgery, two equal groups were created with 40 patients in each group. One group received antibiotics, levocetirizine tablet and another group received antibiotics, levocetirizine tablets along with topical intranasal steroid spray from 1 post operative day till 6 wks. All the patients were followed up on the 5th day, 7th day and 42nd day. On 42nd day, status of tympanic membrane graft, post operative hearing assessment was done and compared between the two groups. Data were entered and analysed using Statistical Package For Social Sciences (SPSS) v21. Result: There were 40 patients who received levocetirizine only starting from the first post operative day and 39 patients received levocetirizine and topical nasal steroid spray. Patients with intact tympanic membrane following surgery were 88.6% and remaining had residual perforation of tympanic membrane. Of the study participants 87.3 % had improvement during post operative hearing assessment. 92.3% of the patients receiving levocetirizine and topical nasal steroid post surgery had intact tympanic membrane on otoscopic examination and there was a significant association with p value of 0.04 Conclusion: Combination therapy with topical intranasal steroid spray, antihistaminics and antibiotics is beneficial compared to antibiotics and antihistaminics in type 1 tympanoplasty in terms of graft intake and improvement in hearing. BJHS 2018;3(1)5 : 377-380